Pemanfaatan Media Digital Untuk Meningkatkan Visibilitas dan Brand Awareness Wisata Edukasi - Meyliana, Anastasia; Rapiyanta, Paulus Tofan; Indriyanti, Indriyanti; Safitri, Lina Ayu (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Digital marketing is a key element in increasing the competitiveness of the tourism industry, including in promoting educational tourism. However, many tourism managers still face obstacles in optimally utilizing digital technology, such as a lack of understanding of digital marketing strategies, limitations in creating creative content, and low social media engagement. These issues hinder the increase in product awareness and brand awareness, so that educational tourism is less well-known to a wider target market. This community service activity aims to improve the skills of tourism managers in creating and managing effective digital marketing content. The methods used include theoretical and practical training, covering digital marketing strategies, graphic design using Canva, writing techniques and creating content materials using AI, and optimizing social media. The results of the activity showed that after the training, partners experienced an increase in understanding and skills in digital marketing. They were able to create more attractive visual content, manage social media more actively, and increase engagement with the audience. The impact is an increase in exposure to educational tourism on social media, which has the potential to increase the number of tourist visits. With the sustainability of the digital marketing strategy that has been implemented, it is hoped that educational tourism can continue to develop and have stronger competitiveness.